2007
DOI: 10.1016/j.cell.2007.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Fluorescence Detection of ERAD Substrate Retrotranslocation in a Mammalian In Vitro System

Abstract: SummarySecretory proteins unable to assemble into their native states in the endoplasmic reticulum (ER) are transported back or “retrotranslocated” into the cytosol for ER-associated degradation (ERAD). To examine the roles of different components in ERAD, one fluorescence-labeled ERAD substrate was encapsulated with selected lumenal factors inside mammalian microsomes. After mixing microsomes with fluorescence-quenching agents and selected cytosolic proteins, the rate of substrate efflux was monitored continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 67 publications
4
98
0
Order By: Relevance
“…Derlin-1 was initially reported to be important for the extraction of MHC class I molecules from the ER membrane in cytomegalovirus-infected cells (Lilley and Ploegh 2004;Ye et al 2004). Reconstitution assay using a fluorescently labeled substrate also showed that Derlin-1 is involved in substrate dislocation, which is independent of Sec61a (Wahlman 2007). The yeast Hrd1p E3 ligase, which interacts with the ERAD substrate via its trans-membrane region, is also a possible candidate (Carvalho et al 2010).…”
Section: Retrotranslocation and Degradationmentioning
confidence: 99%
“…Derlin-1 was initially reported to be important for the extraction of MHC class I molecules from the ER membrane in cytomegalovirus-infected cells (Lilley and Ploegh 2004;Ye et al 2004). Reconstitution assay using a fluorescently labeled substrate also showed that Derlin-1 is involved in substrate dislocation, which is independent of Sec61a (Wahlman 2007). The yeast Hrd1p E3 ligase, which interacts with the ERAD substrate via its trans-membrane region, is also a possible candidate (Carvalho et al 2010).…”
Section: Retrotranslocation and Degradationmentioning
confidence: 99%
“…Juxtaposing the ER factors that prime the misfolded substrates for retro-translocation to the channel itself enables an efficient means of transport. Of note, retro-translocation of the nonglycosylated prepro-␣-factor requires PDI (Gillece et al, 1999;Wahlman et al, 2007) and Derlin-1 (Wahlman et al, 2007). Similarly, the ER-to-cytosol transport of the murine polyomavirus also relies on PDI and Derlin-2 (Lilley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PDI has been implicated in the retro-translocation of misfolded proteins (Gillece et al, 1999;Molinari et al, 2002;Wahlman et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Binding of the base to the 20 S CP activates proteolysis, and the AAA-ATPases of the base facilitate substrate unfolding and delivery into the proteolytic chamber for degradation. In addition, the 19 S RP has been implicated in cytosolic dislocation of ERAD substrates (17,(35)(36)(37); however, the majority of these studies focused on soluble substrates sequestered within the ER lumen. In some cases, dislocation of these substrates was independent of ubiquitination and the action of VCP/p97.…”
Section: Discussionmentioning
confidence: 99%